Intraarticular Tranexamic Acid Decreased Transfusion Rates and Blood Loss in Primary Total Hip Arthroplasty: A Prospective Randomized Double-Blind Placebo-Controlled Trial - Sueajui, MD, Jithayut; Chanalithichai, MD, Nuttawut; Piyapromdee, MD, Urawit; Suksathien, MD, Yingyong (Journal of Southeast Asian Orthopaedics, 2022)
Backgrounds: Total hip arthroplasty (THA) often requires blood transfusion postoperatively. Tranexamic acid (TXA) has been successfully used intravenously to control bleeding. Intraarticular TXA is safe and effective at reducing postoperative bleeding in orthopedic procedures, but there is limited literature regarding its use in THA. The objective of this prospective randomized study was to determine if intraarticular TXA decreased postoperative transfusion rates and bleeding after primary THA. Propose: To study the efficacy of intraarticular tranexamic acid to decrease postoperative transfusion rates and blood loss after primary total hip arthroplasty. Methods: A prospective double-blinded, randomized controlled trial of 135 primary THA of 118 patients investigated the efficacy of intraarticular application of TXA on blood loss compared with a placebo in Maharat Nakhon Ratchasima Hospital during the period from September 2013 to March 2015. Intraarticular TXA (750 mg) was applied after acetabular and femoral canal preparation. The primary outcome was blood transfusion rate, the mean drain blood loss, and total blood loss by Gross formula. Secondary outcomes include the units of blood transfusion, nadir post-operative hemoglobin and hematocrit, hemoglobin and hematocrit concentration change, visual analog scales (VAS), length of hospital stay, and up to 12 weeks follow-up for surveillance complications. Results: Patients in the TXA group insignificantly improved in reduction of transfusion rates (TXA group = 39.7%, Placebo = 55.2%; P-value = 0.07), drain blood loss (TXA group = 535 mL, Placebo = 540mL; P-value = 0.45), and total blood loss by Gross formula (TXA group = 771 mL, Placebo = 757 mL; P-value = 0.59) compared with the placebo. However, the units of blood transfused decreased significantly in the TXA group cases compared to the placebo (TXA = 0.53 units per case, Placebo = 0.88 units per case; P-value=0.035). Visual analog scales (VAS) also reduced significantly in the TXA group (TXA = 3.9, Placebo = 4.7; Pvalue=0.001). There were three complications in the tranexamic acid group (two acute febrile illness and one dislocation) and five in the placebo group (one superficial infection, two acute febrile illness and two dislocation). There was no sciatic nerve irritation from the diluted dose of tranexamic acid used in the study. Conclusions: The use of 750mg intraarticular tranexamic acid in patients undergoing THA does not effectively reduce postoperative blood transfusion rates and bleeding. However, the units of transfusion (units per case) and visual analog scale could be declined statistically significantly.